200 Effect of Long-term Feeding of Deoxynivalenol (DON) Contaminated Diets on Performance of Grower-finisher Pigs - Bosompem, Michael A (J Anim Sci, 2021)
Previous studies examining the effects of deoxynivalenol (DON) intake in pigs have largely focused on young animals or have been over a short period of time. The objective of the present study was to determine the effects of long-term feeding of DON contaminated diets on growth performance of grower-finisher pigs. A total of 240 mixed-sex pigs (35.9 ± 1.1 kg) were group housed in 6 pigs/pen (n = 10/treatment) and were randomly assigned to 1 of 4 dietary treatments for 77 d. Diets consisted of a control diet (CON) containing no DON or a diet containing 1, 3, or 5 ppm DON (DON1, DON3, or DON5) achieved by adding DON-contaminated wheat and wheat screenings at the expense of clean wheat. In the grower period, DON5-fed pigs had reduced average daily gain (ADG) compared to CON, with DON1 and DON3-fed pigs being intermediate P < 0.05). There was no effect of dietary treatment on ADG in the finisher period (P > 0.05). Overall the entire study, DON3 and DON5-fed pigs had similar and reduced ADG (P < 0.05) compared to CON and DON1, which did not differ (P > 0.05). Feed intake was reduced in DON-fed pigs in the finisher period (3.12, 2.97, 2.96, and 2.88 ± 0.05; P< 0.05) and in DON3 and DON5-fed pigs overall (2.62, 2.55, 2.47, 2.47 ± 0.03; P < 0.05) compared to CON, with no overall effect observed in the grower period. There was no effect on feed efficiency in any period (P > 0.05). The decrease in performance resulted in reduced final body weight in DON3 and DON5-fed pigs, compared to CON, with DON1-fed pigs being intermediate (P > 0.05). Overall, the effects of DON-intake on performance were variable and generally occurred rapidly after initial exposure and appear to be largely due to the reduction in feed intake. [Image: see text]